HUBUNGAN AKTIVITAS FISIK DENGAN STATUS GIZI PADA ANAK USIA DIBAWAH 6 TAHUN DI TK PERTIWI KOTA BANGKINANG - Deinike Wanita Marwan; Nurlaila Nurlaila; Evy Eryta; Elvina Zuhir; Risnandar Risnandar (Collaborative Medical Journal, 2023)
Obesity can occur due to an imbalance between energy intake and energy expenditure. Factors that play a role in determining the nutritional status of children are diet and physical activity. The general objective of this study was to determine the relationship between the level of physical activity and nutritional status as assessed based on body mass index in children under 6 years old at Pertiwi Kindergarten, Bangkinang City. This research is a quantitative research that is observational descriptive analytic with a cross sectional approach. The sampling method uses total sampling technique. Data were collected using questionnaires, scales and microtoise to measure body weight and height. This study found that subjects with a normal body mass index slept an average of 11.3 hours, did sedentary activities for 10.90 hours and were active for 1.96 hours a day, while subjects with a body mass index above the average sleeping normally for 13.69 hours, doing sedentary activities for 8.58 hours and doing active activities for 1.13 hours a day. In this study, 60 respondents had a normal body mass index, and 10 respondents had a body mass index who were overweight or obese. There is a significant relationship between physical levels. activity and nutritional status in children under 6 years of age.